The Goettingen minipig as an experimental model in wound-healing studies - Eisler, Wiebke; Held, Manuel; Rahmanian-Schwarz, Afshin; Baur, Jan-Ole; Daigeler, Adrien; Denzinger, Markus (JPRAS Open, 2024)
Background: Deep dermal wounds in extensive burns and chronic wound-healing disorders represent a significant medical problem and require a high level of therapy to reduce the risk of infection and other long-term consequences, such as amputation. A better understanding of the wound-healing processes is essential, and animal models are indispensable to fundamental research. Objective: This study aimed to provide a transparent protocol and prove the effectiveness of an in vivo porcine model using Goettingen minipigs for wound-healing studies. Material and methods: Thirteen female Goettingen minipigs were kept in species-appropriate housing and were treated according to the German law for the protection of animals. The study was performed with permission from the local ethical review committee of animal welfare. The experimental procedure for studying dermal regeneration in 102 full-thickness wounds through clinical observation and histological analysis, focusing on neodermal formation, is described in detail. Results: The Goettingen minipig model proved to be suitable in wound-healing studies. The dermal regeneration was evident and viewable without wound contamination or any rejection reaction. The histological evaluations were also reliable and clearly presented the optimized wound healing of deep dermal wounds using the different therapeutic approaches. Conclusion: Given the great clinical need for alternative or complementary therapies, we considered the Goettingen minipig trial a reliable, ethically justifiable, effective, and reproducible in vivo model for wound-healing studies.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Animal model; Goettingen minipig; Tissue engineering; Wound healing